Improving Bounce Pass Skills in Basketball Games Using the Problem Based Learning Method - Dini Marta Madyana Hari; Wulandari Luthfia; Erwinsyah Riski Fahmi; Cahyono Andik; Pamungkas Hari (Journal of Education Technology and Inovation, 2023)
This research uses a problem-based learning approach with a learning sequence of observation, evaluation, and progress monitoring to measure the improvement of individual bounce pass skills. During the learning process, learners are invited to identify problems or difficulties they face in performing the bounce pass. Collaborate in finding solutions to overcome these problems. Conduct learning and simulation of game situations that allow the application of the "bounce pass" technique with the help and direction of the teacher. The method in this study uses a classroom action research (PTK) approach of observation, evaluation, and progress monitoring to measure the improvement of individual bounce pass skills. The results of this study contribute to the development of effective learning methods in improving technical skills in sports, especially in the context of basketball games, with the skill completeness value increasing from pre 61.5% to 73.1% and increasing 100%. The PBL method has an effect on the development of effective learning methods in improving technical skills in sports, especially in the context of basketball games